Answer
See graph and explanations.
![](https://gradesaver.s3.amazonaws.com/uploads/solution/904f2774-cd03-4b29-ae7d-22284e50f989/result_image/1586023801.jpg?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250118%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250118T043316Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=055f3dbbc3f46c1084fda43a7e5c35fdbbafe75e7ab52f7603c6bed3fdb34cd8)
Work Step by Step
Step 1. Rewrite the equation as
$4y^2+(4x)y+(x^2+10\sqrt 5x-9)$
and let
$a=4, b=4x, c=x^2+10\sqrt 5x-9$
Step 2. Use the quadratic formula $y=\frac{-b\pm\sqrt {b^2-4ac}}{2a}$ to get
$y=\frac{-4x\pm\sqrt {(4x)^2-4(4)(x^2+10\sqrt 5x-9)}}{8}=\frac{-x\pm\sqrt {9-10\sqrt 5x}}{2}$
Step 3. We can graph the equations $y_1=\frac{-x+\sqrt {9-10\sqrt 5x}}{2}$ and $y_2=\frac{-x-\sqrt {9-10\sqrt 5x}}{2}$ as shown in the figure.